2020
DOI: 10.1002/jum.15314
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Axillary Lymph Node Metastasis in Patients With Breast Invasive Ductal Carcinoma With Negative Axillary Ultrasound Results Using Conventional Ultrasound and Contrast‐Enhanced Ultrasound

Abstract: Objectives-The purpose of this study was to establish a scoring system for predicting axillary lymph node metastasis (ALNM) in patients with breast invasive ductal carcinoma with negative axillary ultrasound (US) results. Methods-In this retrospective study, 156 breast invasive ductal carcinoma lesions from 156 women were retrospectively enrolled. The features of conventional US and contrast-enhanced ultrasound (CEUS) qualitative enhancement patterns and quantitative enhancement parameters were analyzed. Subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…Metastatic LNs often exhibit heterogeneous enhancement, slight enhancement, or no enhancement. The sensitivity, specificity, positive predictive value, and negative predictive value were 82%, 91%, 78%, and 92%, which was consistent with the findings of relevant studies (24)(25)(26).…”
Section: Discussionsupporting
confidence: 89%
“…Metastatic LNs often exhibit heterogeneous enhancement, slight enhancement, or no enhancement. The sensitivity, specificity, positive predictive value, and negative predictive value were 82%, 91%, 78%, and 92%, which was consistent with the findings of relevant studies (24)(25)(26).…”
Section: Discussionsupporting
confidence: 89%
“…A previous study revealed that tumor staging was an independent predictor of breast cancer LN metastasis ( 30 ). A tumor size of 20 mm or greater on ultrasound was an independent predictor of LN metastasis ( 31 ). In the present study, however, there was no significant difference in the number of tumors evaluated as T1 and T2/T3 in LN-positive and -negative groups ( p = 0.340), which was similar to the results of the previous study; that is, tumor size on ultrasound was not an independent predictor of axillary LN metastasis ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…19 CEUS is an emerging imaging technology that provides more diagnostic information compared with conventional grayscale ultrasound. 20 CEUS perfusion parameters were found to correlate with vascular endothelial growth factor (VEGF) expression and predictors of poor prognosis, 21 in addition, it can provide excellent predictive value for high-grade malignancy of BC and might help to determine appropriate therapeutic strategies. 22 Although previous studies have explored the correlation between CEUS characteristics and certain histopathological features of BC, 23,24 few studies have focused on the identification of BC molecular subtypes based on CEUS characteristics.…”
mentioning
confidence: 99%
“…In addition, some studies have shown that CEUS can make up for the limitations of color Doppler ultrasound in terms of tumor microvascular differentiation, and realize the possibility of a more precise and even functional diagnosis 19 . CEUS is an emerging imaging technology that provides more diagnostic information compared with conventional gray‐scale ultrasound 20 . CEUS perfusion parameters were found to correlate with vascular endothelial growth factor (VEGF) expression and predictors of poor prognosis, 21 in addition, it can provide excellent predictive value for high‐grade malignancy of BC and might help to determine appropriate therapeutic strategies 22 .…”
mentioning
confidence: 99%